The impact of agricultural biotechnology on supply and land-use. (December 2014) - Barrows, Geoffrey; Sexton, Steven; Zilberman, David
Abstract We use aggregate data to estimate supply, price, land-use, and greenhouse gas impacts of genetically engineered (GE) seed adoption due both to increased yield per hectare (intensive margin) and increased planted area (extensive margin). An adoption model with profitability and risk considerations distinguishes between the two margins, where the intensive margin results from direct 'gene' impacts and higher complimentary input use, and the extensive margin reflects the growing range of lands that become profitable with the GE technology. We identify yield increases from cross-country time series variation in GE adoption share within the main GE crops – cotton, corn and soybeans. We find that GE increased yields 34 per cent for cotton, 12 per cent for corn and 3 per cent for soybeans. We then estimate the quantity of extensive margin lands from year-to-year changes in traditional and GE planted area. If all production on the extensive margin is attributed to GE technology, the supply effect of GE increases from 5 per cent to 12 per cent for corn, 15 per cent to 20 per cent for cotton, and 2 per cent to 40 per cent for soybeans, generating significant downward pressure on prices. Finally, we compute 'saved' lands and greenhouse gases as the difference between observed hectarage per crop and counterfactual hectarage needed to generate the same output without the yield boost from GE. We find that altogether, GE saved 13 million hectares of land from conversion to agriculture in 2010, and averted emissions are equivalent to roughly one-eighth of the annual emissions from automobiles in the US.